1956
DOI: 10.1111/j.1365-2621.1956.tb16965.x
|View full text |Cite
|
Sign up to set email alerts
|

Objective Tests Applicable to Quality Studies of Ice Stored Shrimp

Abstract: Objective quality tests are urgently needed by the shrimp industry to permit distribution and processing of individual catches of shrimp according to their expected storage life.Heretofore, organoleptic measurements of quality have been used almost exclusively for purchasing and grading shrimp products at various stages during their storage life. These tests are very useful for rapid examination of such products. Unfortunately, they are based on personal judgment and consequently result in numerous subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

1972
1972
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 19 publications
(10 reference statements)
1
3
0
2
Order By: Relevance
“…A rapid degradation of nitrogen-containing components has been indicated during spoilage of fishery products as spoilage begins. A trimethylamine nitrogen value of 1.5 mg/100 g of unshelled, headless shrimp has tentatively been specified as an objective index of spoiled shrimp (Baily et al, 1956). STOMte Tine ( DAYS)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapid degradation of nitrogen-containing components has been indicated during spoilage of fishery products as spoilage begins. A trimethylamine nitrogen value of 1.5 mg/100 g of unshelled, headless shrimp has tentatively been specified as an objective index of spoiled shrimp (Baily et al, 1956). STOMte Tine ( DAYS)…”
Section: Resultsmentioning
confidence: 99%
“…Included are acid-soluble orthophosphate, trimethylamine nitrogen, amino nitrogen, extract release volume, pH, and bacterial count. At present, however, organoleptic measurements of quality are used for purchasing and grading seafoods at various stages during their storage life (Baily et al, 1956;Vanderzant and Nickelson, 1971; Cobb and Vanderzant, 1975;Farooqi et al, 1978).…”
mentioning
confidence: 99%
“…Mendes et al, 2002), which is normally higher than in fish and mammalian species due to the higher content of non-protein nitrogenous compounds in crustaceans (Shahidi, 1994). Several authors reported pH 7.80e7.95 to be a critical margin for acceptability of shrimps and prawns (Bailey, Fieger, & Novak, 1956;Chung & Lain, 1979). Yet, as far as edible crab is concerned, the levels of pH acceptability for muscle were higher (around 8.20) and lower for brown meat (above 7.15).…”
Section: Phmentioning
confidence: 96%
“…Bailey et al (1956) consideraram que em pH até 7,70 o camarão mantinha as características de um produto 'fresco", acima deste valor e até 7,95, era considerado de má qualidade, porém aceitável. Valores superiores a 7,95 tornavam desaconselhável o consumo do camarão.…”
Section: Resultados E Discussão Phunclassified
“…Segundo Luna (1971) e Shamshad et al (1990), pH acima de 7,2 e de 7,6, respectivamente, caracterizavam produto não-comestível. Se considerado o limite estabelecido por Bailey et al (1956), pH 7,70, seis lotes (60%) dos analisados (Tabela I) estariam aptos para consumo. Mas em relação ao limite estabelecido por Luna (1971), pH 7,20, apenas dois lotes (20%) dos dez analisados poderiam ser consumidos.…”
Section: Resultados E Discussão Phunclassified